2018
DOI: 10.3390/polym10040431
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Small-Angle Light Scattering for Rheo-Optical Characterization of Chitosan Colloidal Solutions

Abstract: Abstract:In the recent studies on chitosan hydrogels, it was found that understanding both rheological and structural properties plays an important role in their application. Therefore, a combination of two independent techniques was applied to investigate micro-and macroscopic properties of chitosan colloidal system. Studies on viscous properties, as well as the sol-gel phase transition process, were performed using rheological methods coupled with the small angle light scattering (SALS) technique. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…This resulted from the well-known phenomenon in the polymer rheology of the disentanglement of polymer chains and their ordering along the shear field. This phenomenon was also observed for thermosensitive chitosan colloids and described in the previous research of the authors using rheometric measurements combined with small-angle light scattering technique [ 46 ]. This remark is very important since the considered systems must form a polymer network after injection application; changes in their conformation during the flow through the needle may affect both the phase transition conditions and the final mechanical properties of the obtained scaffolds.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This resulted from the well-known phenomenon in the polymer rheology of the disentanglement of polymer chains and their ordering along the shear field. This phenomenon was also observed for thermosensitive chitosan colloids and described in the previous research of the authors using rheometric measurements combined with small-angle light scattering technique [ 46 ]. This remark is very important since the considered systems must form a polymer network after injection application; changes in their conformation during the flow through the needle may affect both the phase transition conditions and the final mechanical properties of the obtained scaffolds.…”
Section: Discussionsupporting
confidence: 79%
“…Xu et al [ 45 ] showed that, with increasing shear rate, the end-to-end distance of the polymer chain increases, indicating its disentanglement. This phenomenon was also observed during rheometric measurements with simultaneous analysis using the small-angle light scattering technique [ 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 71%
“…For this reason, the method proposed by Fredrickson and Larson [61] was used. This theory is based on the order-disorder of block copolymers considering the aggregation of hydrophobic acetylated blocks of chitosan chains in systems with glycerophosphate [34,62], and it can be successfully applied even in the case of systems with dominance of elastic properties over viscous ones. As a consequence, the dependence of temperature as a function of the glycerophosphate concentration with the addition of calcium carbonate was determined.…”
Section: Enrichment With Calcium Ionsmentioning
confidence: 99%
“…The phase transition point of such systems is at a temperature above 50 • C. Thus, it prevents their use as injection scaffolds formed in vivo. The addition of disodium glycerophosphate (Na 2 GP) to the chitosan solution in acid results in the formation of an unstable colloidal system (low value of Zeta potential) and a reduction in the temperature of the sol-gel phase transition point [19,[32][33][34]. The chitosan colloidal solutions obtained by dissolving the polymer in hydrochloric acid are commonly described in the literature, however, the role of glycerophosphate is discussed [19][20][21][22]33,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation